The effect of different composite on Candida albicans biofilm development - Nor Azemi, Siti Nor Humaira; Raja Sahrul Hishan, Raja Izzatun Nisa’; Muhamad Halil, Mohd Haikal; Arzmi, Mohd Hafiz (2019)
Introduction: Candida albicans is an opportunistic microorganism that inhabit oral cavity. It is the most common fungal pathogens isolated from the oral cavity and frequently cause superficial infections such as oral candidiasis. The objectives of the present study are to investigate the effect of caries on C. albicans biofilm formation and to determine biofilm development of C. albicans on different types of composites with the hypotheses that caries isolate C. albicans form more biofilms compared to lab strain and that C. albicans form different cell number in biofilm grown in different composite. Materials and methods: To assess the biofilm forming ability of C. albicans ATCC 32354 and caries iso-late HNFC2 on different composites, 750 μL of YPD broth was pipetted into each well of 12-well plate. Following that 750 μL of C. albicans inoculum prepared in yeast peptone dextrose (YPD) broth was add-ed in the same well. Finally, sterile composite bead (SHOFU, DENTSPLY or SDI) was placed into each well aseptically and incubated at 37 °C for 24 h. Results: The present study has shown that C. albicans HNFC2 has significantly higher cell number on the composites compared to the ATCC (P < 0.05). Meanwhile, in comparison of the three types of compo-sites, DENTSPLY exhibited the least cell number in HNFC2 (7.7 x 10³ cells mL-1) and composite SHOFU was the highest (14.3 x 10³ cells mL-1). Conclusions: In conclusion, C. albicans form different cell number in biofilm grown on different com-posite, and caries isolate C. albicans form more biofilm on composite compared to lab strain.